From darkness, a light shall spring: Zero‐fluoroscopic ablation of supraventricular tachycardia in a pregnant lady. Issue 1 (26th December 2020) - Mohd Said, Mohd Ridzuan; Gian Singh, Sathvinder Singh; Lee, Kuo Ting; Khor, Leet Ming; Chea, Chin Yung; Silveraju, Anand Raj; Mohd Firdaus, Mohd Al‐Baqlish; Karthikesan, Dharmaraj; Muthuppalaniappan, Annamalar Muthu; Abdullah, Abdul Syukur; Ismail, Omar; Narasamuloo, Kantha Rao; et al.
Abstract : Our case illustrated zero‐fluoroscopic approach on AVNRT ablation in a pregnant lady.